Palmitoylation-dependent association with Annexin II directs hepatitis E virus ORF3 sorting into vesicles and quasi-enveloped virions - Xing Liu; Tianxu Liu; Zhen Shao; Xiaoyan Xiong; Shuhui Qi; Junyong Guan; Menghang Wang; Yan-Dong Tang; Zongdi Feng; Lin Wang; Xin Yin (Proceedings of the National Academy of Sciences, 2025)
Historically considered to be nonenveloped, hepatitis E virus (HEV), an important zoonotic pathogen, has recently been discovered to egress from infected cells as quasi-enveloped virions. These quasi-enveloped virions circulating in the blood are resistant to neutralizing antibodies, thereby facilitating the stealthy spread of infection. Despite abundant evidence of the essential role of the HEV-encoded ORF3 protein in quasi-enveloped virus formation, the underlying mechanism remains unclear. Here, we demonstrate that the HEV ORF3 protein possesses an inherent capacity for self-secretion and that palmitoylation at two cysteine residues within the ORF3 N-terminal region is essential for its secretion and quasi-enveloped virus formation. We further found that only palmitoylated ORF3 proteins hijacked Annexin II for transport to the cytoskeleton and are then directed into multivesicular bodies through the nSMase-endosomal sorting complexes required for transport-III pathway for secretion. Finally, we show that infection of gerbils with HEV mutants harboring mutations at palmitoylation sites within ORF3 showed no fecal viral shedding but competent replication in the liver. Our study fills a gap in the understanding of the assembly and release of quasi-enveloped virions mediated by ORF3 and offers the potential for designing therapeutic strategies to control HEV infection.